Knockout of AMPKα2 Blocked the Protection of Sestrin2 Overexpression Against Cardiac Hypertrophy Induced by Pressure Overload - Zhang, Nan; Liao, Hai-Han; Feng, Hong; Mou, Shan-Qi; Li, Wen-Jing; Aiyasiding, Xiahenazi; Lin, Zheng; Ding, Wen; Zhou, Zi-Ying; Yan, Han; Chen, Si; Tang, Qi-Zhu (Frontiers in Pharmacology, 2021)
Objectives: This study intended to investigate whether sestrin2 (Sesn2) overexpression could prevent pressure overload-induced cardiac hypertrophy via an AMPKα2 dependent pathway through conditional knockout of AMPKα2. Methods and results: Sesn2 expression was significantly increased in mice hearts at 2 and 4 weeks after aortic banding (AB) surgery, but decreased to 60%-70% of the baseline at 8 weeks. Sesn2 overexpression (at 3, 6, and 9 folds) showed little cardiac genetic toxicity in transgene mice. Cardiac dysfunctions induced by pressure overload were attenuated by cardiomyocyte-specific Sesn2 overexpression measured by echocardiography and hemodynamic analysis. HE and PSR staining exhibited that Sesn2 overexpression significantly alleviated cardiac hypertrophy and fibrosis in mice hearts induced by pressure overload. Meanwhile, adenovirus-mediated-Sesn2 overexpression markedly suppressed angiotensin II-induced neonatal rat cardiomyocytes hypertrophy in vitro. Mechanistically, Sesn2 overexpression activated AMPKα2 phosphorylation but inhibited mTORC1 phosphorylation. The cardiac protection of Sesn2 overexpression was also via regulating oxidative stress by enhancing Nrf2/HO-1 signaling, restoring SOD activity, and suppressing NADPH activity. Particularly, we first proved the vital role of AMPKα2 in the regulation of Sesn2 with AMPKα2 knockout (AMPKα2-/-) and crossed with Sesn2 transgene mice, since Sesn2 overexpression failed to improve cardiac function, inhibit cardiac hypertrophy and fibrosis, and attenuate oxidative stress after AMPKα2 knockout. Conclusion: This study uniquely revealed that Sesn2 overexpression showed little genetic toxicity in mice hearts and inhibited mTORC1 activation and oxidative stress for protecting against pressure overload-induced cardiac hypertrophy in an AMPKα2 dependent pathway. Thus, interventions through promoting Sesn2 expression might be a potential strategy for treating pathological cardiac hypertrophy and heart failure.